Elaboración de un recetario a base de ají rocoto - Garzón Granja, Gustavo Thomas (2023)
This scientific article aims to motivate the consumption of capsicum pubescens rocoto pepper through the creation of a recipe book to take advantage of its nutritional contribution. The research adopts a mixed approach based on the analysis of the content of 12 recipes which will help promote the consumption of rocoto pepper. In addition, surveys and interviews were carried out with the purpose of collecting information about the knowledge that people have about rocoto chili. As results, it was possible to obtain information and collect 12 recipes from the chefs and restaurant owners who were interviewed. On the other hand, it is highlighted that it will be obtained due to the creation of the recipe book. In conclusion, the elaboration of the recipe book based on rocoto chili allowed to rescue and value the richness of the gastronomic culture related to this traditional ingredient. It was possible to demonstrate the diversity of dishes and culinary techniques that use the rocoto pepper as a protagonist, which contributes to preserve and disseminate the culinary heritage of the region.